Global currents in gender and feminisms : Canadian and international perspectives - Bonifacio, Glenda Tibe, 1963- (Bingley, U.K. : Emerald Publishing Limited, 2017)
This collection examines the ongoing shared struggles of diverse groups of women in Canada and beyond focusing on a diverse range of themes including movements, spaces and rights; inclusion, equity and policies; reproductive labour, work and economy; health, culture and violence; and sports and bodies. Situating Canada as a western society with avowed egalitarian ideals, and based on a 'shared but different' approach, this book highlights the intersectional dimensions of gendered lives and feminist actions for change in both western and non-western contexts. Gender issues and feminist struggles are interconnected internationally and this book examines the Canadian case alongside other countries across Latin America, Africa, Asia, Australasia and Europe to explore the global currents of gender and feminism and its practice. The centrality of gender and the need for feminist praxis remain highly relevant in the 21st Century, whether in western or non-western societies, and this collection provides a comprehensive overview of the international currents for gender equality, empowerment and social justice.
Includes index.
Includes bibliographical references.
Print version record
Keywords: Feminism -- 21st century; Feminism -- Canada; Feminism -- International cooperation